Analisis Isi Pro Kontra Pemberitaan Media Massa di Harian Fajar terhadap Kebijakan Di Rumah Saja - Muhammad Rustam (Universitas Serang Raya, 2022)
The case of Covid-19 has become a global pandemic and is worrying all countries, including Indonesia. To break the chain of virus spread, the government has made policies to work from home, study from home, and worship from home. This policy was then reported in various mass media, including the Fajar daily newspaper which was published in Makassar City. This study aims to find out the direction of the news from being published. The research method used by the researcher in this study is a quantitative method with a content analysis approach and library research. The agenda setting theory is used in this study to statistically describe the provision of policies at home by the government. The population in this study is all news published in the Fajar Daily Newspaper from March 2, 2020 to April 30, 2020. The selected sample is part of the population with a total of 1061 news reports. The results of this study found that 74.5% news contained pro news (supporting the government), while 25.5% contained contra news (not supporting the government). The results of this study using content analysis found that the public is strongly encouraged to sort out information based on their analysis or perspective based on government policies, namely working from home, studying from home, and worshiping from home during the Covid-19 pandemic in Indonesia. This analysis of the pros and cons of this announcement will contribute to the community about how the mass media lead to public opinion.